Large-Scale Gene Expression Signatures Reveal a Microbicidal Pattern of Activation in Mycobacterium leprae-Infected Monocyte-Derived Macrophages With Low Multiplicity of Infection - Leal-Calvo, Thyago; Martins, Bruna Leticia; Bertoluci, Daniele Ferreira; Rosa, Patricia Sammarco; Camargo, Rodrigo Mendes de; Germano, Giovanna Vale; Brito de Souza, Vania Nieto; Pereira Latini, Ana Carla; Moraes, Milton Ozório (Frontiers in Immunology, 2021)
Leprosy is a disease with a clinical spectrum of presentations that is also manifested in diverse histological features. At one pole, lepromatous lesions (L-pole) have phagocytic foamy macrophages heavily parasitized with freely multiplying intracellular Mycobacterium leprae. At the other pole, the presence of epithelioid giant cells and granulomatous formation in tuberculoid lesions (T-pole) lead to the control of M. leprae replication and the containment of its spread. The mechanism that triggers this polarization is unknown, but macrophages are central in this process. Over the past few years, leprosy has been studied using large scale techniques to shed light on the basic pathways that, upon infection, rewire the host cellular metabolism and gene expression. M. leprae is particularly peculiar as it invades Schwann cells in the nerves, reprogramming their gene expression leading to a stem-like cell phenotype. This modulatory behavior exerted by M. leprae is also observed in skin macrophages. Here, we used live M. leprae to infect (10:1 multiplicity of infection) monocyte-derived macrophages for 48 h and analyzed the whole gene expression profile using microarrays. In this model, we observe an intense upregulation of genes consistent with a cellular immune response, with enriched pathways including peptide and protein secretion, leukocyte activation, inflammation, and cellular divalent inorganic cation homeostasis. Among the most differentially expressed genes (DEGs) are CCL5/RANTES and CYP27B1, and several members of the metallothionein and metalloproteinase families. This is consistent with a proinflammatory state that would resemble macrophage rewiring towards granulomatous formation observed at the T-pole. Furthermore, a comparison with a dataset retrieved from the Gene Expression Omnibus of M. leprae-infected Schwann cells (MOI 100:1) showed that the patterns among the DEGs are highly distinct, as the Schwann cells under these conditions had a scavenging and phagocytic gene profile similar to M2-like macrophages, with enriched pathways rearrangements in the cytoskeleton, lipid and cholesterol metabolism and upregulated genes including MVK, MSMO1, and LACC1/FAMIN. In summary, macrophages may have a central role in defining the paradigmatic cellular (T-pole) vs. humoral (L-pole) responses and it is likely that the multiplicity of infection and genetic polymorphisms in key genes are gearing this polarization.